OPEN LABEL COMPARATIVE CLINICAL TRIAL OF DVIPANCHAMOOLADI TAILA AND KSHEERABALA TAILA MATRA VASTI IN THE MANAGEMENT OF LOW BACK ACHE (International Journal of Ayurveda and Pharma Research, 2016)
Low back pain is a leading cause of disability, interferes with quality of life and work performance, and is the most common reason for medical consultations. Few cases of back pain are due to specific causes; most cases are non-specific. The most common presentation is acute back pain and is usually self-limiting, lasting less than three months regardless of treatment. Chronic back pain is a more difficult problem, which often has strong pathological and psychological overlay like work dissatisfaction, boredom, and a generous compensation system contribute to it. Among the diagnoses lumbar spondylosis is blamed. No single treatment is superior to others; even surgery is seldom successful at alleviating it. Hence a clinical study was conducted on 30 patients with classical sign and symptoms of Katigraha (LBA) with an aim to find out the effectiveness of Dvipanchamooladi taila Matra basti (oil enemata of an indigenous compound). The patients were randomly divided in to two groups 15 patients in each. Group I (Trial) administered with Dvipanchamooladi taila matra basti and Group II (Control) – Ksheerabala taila Matra basti (enemata prepared by processing Sida Cordifolia root with milk and sesame oil) for a total period of nine days. The trial drug being potentiated by its inherent properties like anti-inflammatory, anodyne etc. exhibited favorable result with an effectiveness of 87.30% to reduce the sign and symptom of low back ache & the effect of the trial therapy were statistically highly significant with a p-value of > 0.01 in the management of Low back ache.